1984
DOI: 10.1051/rnd:19840407
|View full text |Cite
|
Sign up to set email alerts
|

Studies on acrosome labelling of mammalian spermatozoa by radioactive sugars

Abstract: Summary. The localization of glycoprotein synthesis and storage was studied during acrosome formation in guinea-pig using fine-structure autoradiography after ( 3 H1-fucose incorporation. Three days after ( 3 H1-fucose injection, labelling in spermatids was concentrated in the matrix of developing acrosomes, and it was evident that the fucosylation of acrosomal glycoproteins largely overshadowed the fucosylation of other spermatid glycoproteins.Acrosin labelling and its quantitative relation to labelling of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In all species the staining with UEA I, which indicates the distribution of fucose residues, covered the whole sperm head. This observation is consistent with autoradiographic evidence for 3H-fucose distribution in guineapig spermatids over the acrosome (Kopecny et al, 1984), where it may become incorporated into acrosin. Besides the acrosome, 3Hfucose is possibly incorporated into multiple sites in the developing spermatocytes and spermatids, since at least 16 different glycoproteins have been identified (Grootegoed et al, 1982).…”
Section: Discussionsupporting
confidence: 89%
“…In all species the staining with UEA I, which indicates the distribution of fucose residues, covered the whole sperm head. This observation is consistent with autoradiographic evidence for 3H-fucose distribution in guineapig spermatids over the acrosome (Kopecny et al, 1984), where it may become incorporated into acrosin. Besides the acrosome, 3Hfucose is possibly incorporated into multiple sites in the developing spermatocytes and spermatids, since at least 16 different glycoproteins have been identified (Grootegoed et al, 1982).…”
Section: Discussionsupporting
confidence: 89%
“…Using an indirect fluorescence staining technique acrosin, or its precursor proacrosin, was found to be synthesized during early spermiogenesis (Phi- Florke et al, 1983;Adahm et al, 1989). Kopecny et al (1984) used indirect labeling with 3Hfucose to localize proacrosin or its derivatives in the acrosomal matrix of guinea pig and rabbit spermatids 'D 1991 WILEY-LISS, INC. and suggested that these proteins were apparently the major targets for acrosomal protein glycosylation. de Vries et al (1985) localized acrosin in the equatorial segment of ejaculated porcine sperm and suggested that a change in acrosin localization was part of the process of epididymal maturation in porcine sperm.…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkable that acrosomal proacrosin of guinea pig, the precursor of the acrosin, a protease involved in fertilization, is a fucosylated glycoprotein (Anakwe et al 1991). The presence of Fuc in acrosome of guinea pig has also been shown by autoradiographs (Kopecny et al 1984). UEA-I histochemistry of Xenopus testis.…”
Section: Discussionmentioning
confidence: 92%